A comparison between combined open bypass revascularization and free tissue transfer versus endovascular revascularization and free tissue transfer for lower limb preservation. Issue 7 (11th September 2015) - Hsu, Honda; Chang, Chien‐Hwa; Lee, Cheng‐Yung; Huang, Chieh‐Chi; Mark Chiu, Chih‐Hung; Lin, Chih‐Ming; Lee, Jiunn‐Tat; Chien, Sou‐Hsin
<x xml:space="preserve">Abstract</x> Background Extensive defects of the lower limb as a result of diabetes and peripheral vascular disease require multidisciplinary treatment. Numerous studies with regards combining vascular bypass surgery and free tissue reconstruction of the lower limb had been published. However the trend has evolved toward a combination of endovascular revascularization and free flap reconstruction. The aim of this study was to compare the safety and efficacy of this combination of treatment to the traditional combination of bypass surgery and free tissue reconstruction. Methods All patients who had undergone vascular bypass surgery and free tissue reconstruction of the lower limb as well as those who had undergone endovascular angioplasty with free tissue transfer for lower limb preservation, over a 10‐year period was included in this study. Results A total of 46 patients that underwent limb preservation were included in this study, 22 patients underwent open bypass revascularization and free flap transfer and 24 patients underwent endovascular revascularization and free tissue transfer. There were no differences between the two methods with regards to age, sex, defect size, TransAtlantic InterSociety Consensus level, Wagner classification, length of hospitalization, limb preservation rate, total flap necrosis rate, and partial flap necrosis rate. More importantly, there was no significant difference in the limb preservation rate (P = 0.14). Conclusion In this study we found that the safety and the success rate of lower limb preservation using a combination of endovascular revascularization and free tissue reconstruction is comparable to using a combination of bypass surgery and free tissue transfer. © 2015 Wiley Periodicals, Inc. Microsurgery 35:518–527, 2015.